An Analysis of the Perceptions of UTM Islamic Faculty Students Regarding Online Reviews and Ratings in Building Shopping Trust in the Shopee Marketplace - Muawanah, Muawanah; Fatonah, Fatonah; Afiyanta Wulandari; Yusnia, Yusnia; Wahyudi Dwi Putra Romadhon; Siti Zubaidah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
The development of digital technology has transformed consumer behavior, including that of students, in online shopping. One of the factors influencing purchasing decisions is online reviews and ratings on marketplace platforms. This study aims to understand the perceptions of students from the Faculty of Islamic Studies at Universitas Trunojoyo Madura (UTM) regarding online reviews and ratings in building trust when shopping on Shopee. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews and observations of students who are active Shopee shoppers. The data were analyzed through data reduction, data presentation, and drawing conclusions to identify patterns of student perceptions. The findings reveal that students view online reviews and ratings as important and credible sources of information in evaluating products and sellers on Shopee. Positive reviews and ratings build a sense of security and enhance students’ trust in making transactions, while negative reviews trigger greater caution in shopping. These findings indicate that the quality of information in reviews and ratings plays a significant role in shaping consumer trust, particularly among students engaging in online shopping.